Ferroelectric α‐In2Se3 Wrapped‐Gate β‐Ga2O3 Field‐Effect Transistors for Dynamic Threshold Voltage Control. (26th May 2021) - Yang, Jeong Yong; Yeom, Min Jae; Park, Youngseo; Heo, Junseok; Yoo, Geonwook
Abstract: Indium selenide (α‐In2 Se3 ), which is a recently emerging ferroelectric semiconductor, can solve a major hindrance to applications of an ultra‐wide bandgap beta‐gallium oxide (β‐Ga2 O3 ) semiconductor. Here, ferroelectric α‐In2 Se3 wrapped‐gate β‐Ga2 O3 field‐effect transistors (FETs) for dynamic threshold voltage ( V TH ) control is demonstrated. The dry‐transferred α‐In2 Se3 layer is wrapped around β‐Ga2 O3 channel, which allows efficient electrostatic gate modulation. Thus, the ferroelectricity of α‐In2 Se3 and a thin native oxide interlayer formed at the interface between β‐Ga2 O3 and α‐In2 Se3 can provide effective V TH control. Applying a positive voltage pulse to the gate electrode induces positive V TH shift; hence, the device can be even changed from depletion to enhancement (E‐) mode. The E‐mode β‐Ga2 O3 FET exhibits steep‐subthreshold slope with a negligible hysteresis. The V TH of E‐mode can be further modulated by applying back‐gate bias, and electrical performance can be enhanced via dual‐gate operation. The approach demonstrates an energy efficient β‐Ga2 O3 ‐based switching device architecture integrated with ferroelectric van der Waals 2D materials. Abstract : A dynamic threshold voltage control is demonstrated in ferroelectric indium selenide (α‐In2 Se3 ) wrapped‐gateBeta‐gallium oxide (β‐Ga2 O3 ) field‐effect transistors. The ferroelectricity of α‐In2 Se3 and a native oxide interlayer formed at the interface provides efficient electrostatic gate modulation and thus threshold voltage control. The approach demonstrates an energy efficient β‐Ga2 O3 ‐based switching device architecture integrated with ferroelectric van der Waals 2D materials.